The Materialist Foundations of Politics: A Critique of the Book State and Civil Society - Hamid Malekzadeh; Ahmad Khaleghi damghani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
From which point of view should one think about a system of thought or a current of thought in the life of a political thinker? This is the question that will determine the final analysis of how we deal with the various philosophical-political apparatuses. A confrontation that has, more than anything else, within itself the specific intentions of the person who is describing a system of thought, as well as the issues that have necessitated a particular theory for the narrator. Any form of encountering a text, for the person who is writing about, is a search for an answer that must be presented to the concrete issues of political life at this point in time and space. It is with this premise that I try to write about some of the prison notes of the Italian thinker and political activist Antonio Gramsci. A collection for Persian speakers entitled State and Civil Society, translated by Abbas Milani, has been presented to the market by Akhtaran Publications. I will try to make this study based on an understanding of the concept of politics as a unifying factor to this part of Gramsci's writings,